Can Stray Cats Be Reservoirs of Antimicrobial Resistance? - Valeria Gargano; Delia Gambino; Tiziana Orefice; Roberta Cirincione; Germano Castelli; Federica Bruno; Paolo Interrante; Mariangela Pizzo; Eva Spada; Daniela Proverbio; Domenico Vicari; Marília Salgado-Caxito; et al. (Veterinary Sciences, 2022)
The emergence and spread of antimicrobial resistance (AMR) is a global problem that requires a One Health approach. Despite several studies have reported the role of companion animals as reservoirs of AMR, limited information is available regarding the role of cats in the circulation of AMR. In this study, we evaluated the phenotypic and genotypic profile of 75 Escherichia coli isolated from rectal swabs and fecal samples of 75 stray cats (living in solitary or in a colony) sampled in Palermo (Sicily, Italy), to determine whether these animals may participate in the spread of AMR. Susceptibility to 8 antibiotics was tested using Minimum Inhibitory Concentration assays, while the presence of the common antibiotic resistance genes blaTEM, blaCTX-M, tet(A), and tet(B) was investigated by PCR. From the 75 E. coli isolates analyzed, 43% were resistant to at least one of the eight antibiotics tested, with 31% of the isolates resistant to ampicillin, 23% to cefotaxime, 21% to tetracycline, 20% to cefazolin, and 17% to amoxicillin/clavulanic acid. Most isolates harbored the blaTEM gene (29%), followed by blaCTX-M (23%), tet(A) (21%), and tet(B) (20%). Our results confirm the fecal carriage of antibiotic-resistant E. coli and clinically relevant resistance genes in stray cats. This study highlights the potential role of stray cats in the spread of AMR in urban environments, emphasising the need to better understand their role in AMR circulation when planning strategies to combat it.